The Association Between Women’s Perceptions of Professional Support and Problems Experienced on Breastfeeding Cessation: A Western Australian Study - Hauck, Yvonne; Fenwick, J.; Dhaliwal, Satvinder; Butt, Janice; Schmied, V. (Sage Science Press, 2011)
A cross-sectional survey was used to determine the association among women’s breastfeeding problems, their perceptions of support from midwives and child health nurses, and breastfeeding cessation in the first 10 weeks postbirth in a sample of Western Australian women (N = 2669). Primiparous women (75.8%) experienced significantly more problems that multiparous women (52.6%). Although 78.8% of all women agreed or strongly agreed that staff were helpful with feeding, 53.4% confirmed that different midwives offered different feeding advice; however, receiving different advice from midwives around feeding was not associated with breastfeeding cessation. Differences in breastfeeding cessation were associated with parity. Primiparous women’s cessation was associated with experiencing any breastfeeding problems, unhelpful hospital midwives, and unhelpful information from child health nurses, whereas for multiparous women, this included 2 or more breastfeeding problems, not being able to choose when to feed, and unhelpful information from child health nurses.